1986
DOI: 10.1111/j.1600-0447.1986.tb06283.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric diagnostic categories in Saudi Arabia

Abstract: This study involves 324 new cases referred to the Psychiatric Department of King Faisal University, Dammam, Saudi Arabia, over a period of 6 months. Men outnumbered women, which is in contrast to most Western studies. There was a preponderance in the younger age groups. The interaction of cultural factors and the rapid urbanization of the Saudi society may to some extent explain the pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 5 publications
2
2
1
Order By: Relevance
“…The present study examined psychiatric morbidity in psychiatry unit of a tertiary care hospital during Hajj time in Makkah Al Makkarmah. The finding of males' predominance in our study is similar with studies done in Saudi Arabia (Jeddah [4], and Dammam [5]) and other Arab countries (Jordan [6] and Kuwait [7]), while it is in contrast to studies in western [8] and other countries like Nigeria [9] and Pakistan [10,11]. An explanation for this finding could be that our sample was a mixed sample consisting of patients from different countries, but greater proportion was from Saudi Arabia (48%) and other Arab countries (17%) where males present to psychiatric facilities more than women as found in various studies 4-7], indicating importance of cultural factors in treatment seeking behavior.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study examined psychiatric morbidity in psychiatry unit of a tertiary care hospital during Hajj time in Makkah Al Makkarmah. The finding of males' predominance in our study is similar with studies done in Saudi Arabia (Jeddah [4], and Dammam [5]) and other Arab countries (Jordan [6] and Kuwait [7]), while it is in contrast to studies in western [8] and other countries like Nigeria [9] and Pakistan [10,11]. An explanation for this finding could be that our sample was a mixed sample consisting of patients from different countries, but greater proportion was from Saudi Arabia (48%) and other Arab countries (17%) where males present to psychiatric facilities more than women as found in various studies 4-7], indicating importance of cultural factors in treatment seeking behavior.…”
Section: Discussionsupporting
confidence: 92%
“…Higher rates (52%) were in young adults (25-44), both in males and females. This agrees with findings from studies in Saudi Arabia [5], other Arab countries as in Jordan [6,12] and Egypt [13], and non-Arab countries as Pakistan [10], South Africa [14], and the United States [15]. The reasons for this could be that they are more prone to stress from marital or family conflicts and work pressures, and these factors have been seen as risk factors for psychiatric disorders [16,17].…”
Section: Discussionsupporting
confidence: 89%
“…A clear preponderance of males was also observed in the total sample and among patients with AD. This is contrary to the findings of similar studies that reported higher prevalence rates for dementia among females in several geographical areas and these differences were clear among the oldest age groups [34]. These results may not reflect the true prevalence of dementia of course.…”
Section: Discussioncontrasting
confidence: 99%
“…Reviewing the prevalence of dementia in community studies, Lopes and Bottino, 2002 [34] observed that AD was the most prevalent cause of dementia followed by VD and MD in all geographic regions researched. Mixed dementia represents a frequent pathology in older people where both degenerative and vascular pathology present in the same time.…”
Section: Discussionmentioning
confidence: 99%
“…However, the situation is complex from the data emerging from Arab/Islamic countries. In clinical setting, the males tend to outnumber females in psychiatric care seeking which could be attributed to the increased severity in males [ 42 ] However, in community surveys, there is evidence that women tend to have high propensity to some mental illness [ 43 ] though their presentation may be 'masked' due to certain socio-cultural factors [ 44 ]. In paternalistic society, male in their public front are sanctioned not to appear weak.…”
Section: Discussionmentioning
confidence: 99%